A STUDY ON SCORES OF PROOF AND DEMONSTRATIVE QUESTIONS – THE CASE OF MALAYSIAN UNIVERSITY STUDENTS IN A JOINT DEGREE PROGRAM BETWEEN JAPAN AND MALAYSIA - Yu, Sengoku (PEOPLE: International Journal of Social Sciences, 2015)
In a joint degree program between Japan and Malaysia, Malaysian university students were not necessarilygood at proof and demonstrative questions in the subjects of fundamental mathematical sciences compared with Japanese university students because they had seldom solved such questions. According to the result of tests, it was suggested that the amount of Japanese to write did not affect the scores of the questions and that sorting parts of sentences of proofs appropriately was more useful for improving their scores than writing all sentences of proofs. Lastly, it was proposed that Malaysian students should solve those kinds of questions from secondary education.